The Effect of Gender and the Internet on the Level of Corruption in ASEAN 5 (1997-2019) - Indah Susilowati; Olivia Fachrunnisa; Nugroho Sumarjiyanto BM (Media Ekonomi dan Manajemen, 2021)
The level of corruption in ASEAN countries, especially ASEAN 5, namely Indonesia, Malaysia, Thailand, Vietnam, and the Philippines, although gradually declining but still in the high category. This study aims to analyze the factors that influence the level of corruption in ASEAN-5 countries (Indonesia, Malaysia, Thailand, Vietnam, and the Philippines). The level of corruption is proxied using the Corruption Perception Index (CPI), while the independent variable is internet users, and gender is proxied by female labor force participation and male labor force participation. The results show that the increasing number of internet users will reduce the level of corruption as indicated by the increased CPI value. As for gender, increasing female labor force participation will reduce the level of corruption, but the opposite result is shown by the participation of the male labor force. The policy implication of this study is the need to expand the use of the internet and provide wider opportunities for women to work, especially in public offices, to reduce the level of corruption